Ukraine : accelerating the transition to market : proceedings of an IMF/Workd Bank seminar - Cornelius, Peter, 1960-; Lenain, Patrick; International Monetary Fund.; World Bank. (Washington, DC : International Monetary Fund, 1997)
The papers cover the medium-term macroeconomic framework; wages, poverty, and social safety net reform; private sector development; trade policies and sectoral reforms; and institution building and good governance in Ukraine.
Papers presented at an IMF-World Bank seminar held in Washington, D.C. on July 9, 1996.
Includes bibliographical references.
oif 09/11/15
Loan
Keywords: Ukraine -- Economic policy -- 1991- -- Congresses; Post-communism -- Economic aspects -- Ukraine -- Congresses; Ukraine -- Economic conditions -- 1991- -- Congresses; Ukraine -- Social policy -- Congresses